2019
DOI: 10.5194/acp-2018-1226
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simulation of the radiative effect of haze on urban hydrological cycle using reanalysis data in Beijing

Abstract: <p><strong>Abstract.</strong> Although, air pollution modifies local air temperatures and boundary layer structure in urban areas, little is known about its effects on the urban hydrological cycle. To explore this, changes in the urban surface water balance during different haze levels are modelled in Beijing using the Surface Urban Energy and Water Balance Scheme (SUEWS), forced by reanalysis data. The pollution levels are classified using aerosol optical depth observ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The advantage of SUEWS when compared to other urban land surface schemes is that it contains a parameterization for downward long‐wave radiation (Loridan et al, ), and it does not have separate tiles for urban and vegetation surface fractions, but rather a dynamic interaction between the surface types is allowed. SUEWS has demonstrated good performance against hydrological observations, and EC‐measured turbulent sensible and latent heat fluxes in several cities in Europe, North America, and Asia (e.g., Alexander et al, ; Ao et al, ; Järvi et al, , ; Kokkonen et al, , ; Ward et al, ).…”
Section: Model Descriptionmentioning
confidence: 99%
“…The advantage of SUEWS when compared to other urban land surface schemes is that it contains a parameterization for downward long‐wave radiation (Loridan et al, ), and it does not have separate tiles for urban and vegetation surface fractions, but rather a dynamic interaction between the surface types is allowed. SUEWS has demonstrated good performance against hydrological observations, and EC‐measured turbulent sensible and latent heat fluxes in several cities in Europe, North America, and Asia (e.g., Alexander et al, ; Ao et al, ; Järvi et al, , ; Kokkonen et al, , ; Ward et al, ).…”
Section: Model Descriptionmentioning
confidence: 99%
“…Additionally, Cao et al (2016) found a strong correlation between high concentrations of particulate matter over urban areas and the nocturnal UHI for several megacities in China due to enhanced atmospheric absorption and re-emission of LW radiation back to the surface, reducing the evening cooling rate. The ADMS-Urban radiation model does not account for nocturnal warming effects from haze pollution, which has been shown to change surface energy and water partitioning in Beijing (Kokkonen et al, 2019).…”
Section: Case Surface Parameters Ahesmentioning
confidence: 99%
“…Additionally, Cao et al (2016) found a strong correlation between high concentrations of particulate matter over urban areas and the nocturnal UHI for several megacities in China due to enhanced atmospheric absorption and re-emission of LW Beijing (Kokkonen et al 2019).…”
mentioning
confidence: 98%